KULATHA: THERAPEUTIC APPROACH- A COMPREHENSIVE REVIEW - Shobhana, *MC; Kulkarni, Medha (International Journal of Ayurveda and Pharma Research, 2017)
Ayurveda for the achievement of long, happy and healthy life has described Trayopasthamba (three sub pillars of life) - Ahara, Nidra and Brahmacharya. Among these Ahara is considered as the foremost sustainer of life. The classics have enumerated various food articles which come under the purview of food as well as medicine. Kulatha is one such dietary article having multiplicity in use from time immemorial. It can be utilized in different therapeutic conditions as food and also as medicine. They are good sources of proteins, which help to supplement cereals by improving their protein nutritive value. They also provide optimum quantities of minerals, vitamins and dietary fibre. It can be used as medicine both internally and externally. From Vedic period onwards different Ayurvedic samhitas has mentioned the pharmacological properties of Kulatha. It has been included under the Pathyas of many diseases such as Prameham, Amavatam, Swasam etc. In Ayurvedic classics under the Kritannakalpana supa, Holaka and Yusha are mentioned with Kulatha. Different preclinical and clinical trials has proved Kulatha as non toxic and therapeutically effective. Kulatha is cost effective and can be useful for the prevention as well as for the duration of diseases.